Implementasi Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik Terkait Pidana Penghinaan dan Pencemaran Nama Baik - Pulmer Situmeang; Sagung Putri M. E. Purwan (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
This study aims to examine the Implementation of Punishment related to Contempt and Defamation in Law Number 19 of 2016 concerning ITE (Electronic Information and Transactions). The presence of this law was initially expected to be able to answer the challenges of the times by containing a criminal formulation of individual legal relations through social networks. However, Article 27 Paragraph (3) on Contempt and Defamation is actually a rubber article that is multi-interpreted and negatively affects free speech. It is studied using normative methods and focuses on the applicable law and connects it through legal concepts to analyze legal issues. From the results of the research that has been studied, it shows that the use of absolute offenses can make ITE cases increase and there must also be revisions in some articles of defamation tend to be used multi-interpretation with the subjective authority of law enforcement officials to promote freedom of expression in public.